Long-term effects of subsidies on firm growth: introducing the concept of outcome additionality - Björn Goerke; Son̈ke Albers (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
Public agencies provide subsidies for small and medium sized businesses (SMEs) to foster their development in terms of employment and sales. Although input and output additionality have been researched intensively little is known about the actual long-term effects of subsidies on SME growth. Relying on a unique dataset of actual SMEs we provide a means of evaluating whether subsidies lead to the expected positive long-term effects. We apply a specifically designed 3-stage-effects-model (3SEM) from the input of resources to the final outcome. The results imply that the effects of subsidies differ across types: While R&D grants unfold enduring positive effects other subsidies like corporate matchmaking might even harm companies.
Keywords: L2; H2; O3; 330; subsidies; additionality; innovation